Antidepressant use in suicides: a case-control study from the Friuli Venezia Giulia Region, Italy, 2005–2014 - Castelpietra, Giulio (Eur J Clin Pharmacol, 2017)
PURPOSE: To compare the use of antidepressant (AD) classes and compounds in individuals who committed suicide and in controls from the general population and to assess to what extent adherence and current use of different AD classes can affect the risk of committing suicide. METHODS: Individual data on suicide, diagnoses and AD use in Friuli Venezia Giulia from 2005 to 2014 were obtained from the Regional Social and Health Information System. All suicides that had at least one prescription of AD in the 730 days before death (N = 876) were included as cases. Each case was matched with regard to age and sex with five controls from the general population. The association between suicide and AD use was assessed using conditional logistic regression analysis. RESULTS: Almost 70% of all suicides occurring in the10-year period had been prescribed AD. Selective serotonin reuptake inhibitors (SSRIs) accounted for more than the 90% of the prescriptions, with paroxetine the most prescribed AD. All AD compounds and classes were not associated with a higher suicide risk, with the exception of SSRI (OR = 1.6). A decreasing trend in suicide risk was observed when adherent subjects or current AD users were compared to the others. CONCLUSIONS: AD treatment is an important factor for preventing suicide, since the use of AD at adequate dosage and for a proper duration was associated with a lower suicide risk. The proper use of AD should be ascertained by physicians, particularly in a primary care context. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00228-017-2236-0) contains supplementary material, which is available to authorized users.